Code Mixing and Code Switching in The Classroom Interaction - Meristika Moetia (English Education Journal, 2018)
This case study was carried out based on the issue of using code mixing and code switching in teaching English that specifically to find out the frequent type of code mixing and code switching and to observe the benefit and drawback of using them in the English foreign language classroom interaction.  In collecting the data for this study, observation sheet and interview guide were used as the research instruments. The teacher and 28 students were observed in one meeting by using a video recorder to record all conversations and interactions in the classroom. The teacher-interview session was done right after the observation, and this interview was also recorded by using an audio recorder. All the results were then transcribed and analyzed by using the pattern which is proposed by Musyken (2000) and Poplack (2000). The result revealed that the English teacher and students used two types of code mixing and three types of code switching in their classroom interaction. From the result of interview with the teacher it was found that the teacher did these kinds of codes to cover up the lack of target language proficiency of students and to make the process of transferring knowledge run smoothly and effectively in the class. Besides, she also admit that excessive mixing and switching in Bahasa Indonesia and less in English could make students hard to read and spell English words well and make them unaware and lazy to use English during the process of teaching and learning in the classroom.